Determination of subtypes of Blastocystis sp. in Chilean patients with and without inflammatory bowel syndrome, A preliminary report. (February 2020) - Peña, Sebastián; Carrasco, Gabriela; Rojas, Pamela; Castillo, Douglas; Ozaki, Luiz S.; Mercado, Rubén
Abstract: Background & methods: Blastocystis sp. is one of the most prevalent unicellular eukaryote of the human large intestine in Chile and worldwide. It is classified in subtypes (STs), where using the polymorphic sequences of its 18S rRNA genes currently recognizes 22. STs 1–9 and ST12 have been reported in humans. It has been hypothesized that different STs of Blastocystis sp. differentially affect the clinical severity of the digestive disease in Irritable Bowel Syndrome (IBS) patients, but more studies ar4e needed to establish this statement. To contribute in the elucidation of the potential relationship between Blastocystis sp. subtypes and IBS severity, 37 IBS patient fecal samples were collected at hospitals in Santiago (Chile) and were screened for the presence of vacuolated forms of Blastocystis sp. by using conventional microscopy. Positive samples were submitted to PCR and sequencing for determining STs. The same procedure was performed in fecal samples from five non-IBS Blastocystis sp. carriers for preliminary comparative purpose. Results and discussion: Four out of the 37 samples from the IBS patients were found positive for Blastocystis sp. (10.81%) by using microscopy. The presence of this microorganism in these four samples were confirmed by PCR and sequencing. Subtypes and their respective closest match alleles were searched and the ST1, ST2 and ST4 subtypes were found in these patients. ST4 subtype is scarcely detected in South America countries, being reported previously only in Colombia and Brazil. In this ST4 subtype we determined the allele 42 which is the most frequent allele observed in human Blastocystis isolates. In the non-IBS individuals' carriers, three subtypes were found: ST1, ST2 and ST3, even belonging to the same family group. Closest match alleles: 2, 12 and 34 here detected were also commonly reported globally. Instead of the small number of IBS patients studied here, the frequency of blastocystosis detected (10.81%) was lower than the prevalence of Blastocystis sp. infections described for the Chilean general population (30.4%). In Chile, clear correlation of Blastocystis sp. subtypes and IBS severity is still lacking with this study but it may lead and contribute to a better understanding of its pathogenicity and worldwide epidemiology.